Breslow Intermediates from a Thiazolin‐2‐ylidene and Fluorinated Aldehydes: XRD and Solution‐Phase NMR Spectroscopic Characterization. (5th July 2019) - Paul, Mathias; Neudörfl, Jörg‐M.; Berkessel, Albrecht
Abstract: The first generation and X‐ray diffraction (XRD) analysis of a crystalline Breslow intermediate (BI) derived from a thiazolin‐2‐ylidene, that is, the aromatic heterocycle present in vitamin B1, is reported. Key to success was the combined use of pentafluorobenzaldehyde and a thiazolin‐2‐ylidene carrying an enol‐stabilizing dispersion energy donor as N‐substituent. A so‐called primary intermediate (PI) could be isolated in protonated form (pPI) as well and analyzed by XRD. Furthermore, the first stable BI derived from an aromatic thiazolin‐2‐ylidene and an aliphatic aldehyde (trifluoroacetaldehyde) was prepared and characterized by NMR spectroscopy in solution. When switching to a saturated thiazolidin‐2‐ylidene, reaction with pentafluorobenzaldehyde afforded a new BI in solution (NMR spectroscopy). Attempts to crystallize the latter BI resulted in the isolation of a novel thiazolidin‐2‐ylidene dimer that had undergone rearrangement to a hexahydro[1, 4]‐thiazino[3, 2‐b]‐1, 4‐thiazine. Abstract : Bei der Vitamin‐B1 ‐katalysierten Umpolung entsteht ein Breslow‐Intermediat (BI) aus einem aromatischen Thiazolin‐2‐yliden und dem Substrataldehyd. Die Kombination eines N ‐Dipp‐substituierten Thiazolin‐2‐ylidens mit Pentafluorbenzaldehyd ergab ein BI, das durch XRD charakterisiert wurde. Mit Trifluoracetaldehyd entstand das erste von einem Thiazolin‐2‐yliden und einem aliphatischen Aldehyd abgeleitete BI; dieses wurde NMR‐spektroskopisch charakterisiert.